Diversity of Sinorhizobium (Ensifer) meliloti Bacteriophages in the Rhizosphere of Medicago marina: Myoviruses, Filamentous and N4-Like Podovirus - Cubo, María Teresa; Alías-Villegas, Cynthia; Balsanelli, Eduardo; Mesa, Dany; de Souza, Emanuel; Espuny, María Rosario (Frontiers in Microbiology, 2020)
Using different Sinorhizobium meliloti strains as hosts, we isolated eight new virulent phages from the rhizosphere of the coastal legume Medicago marina. Half of the isolated phages showed a very narrow host range while the other half exhibited a wider host range within the strains tested. Electron microscopy studies showed that phages phiort18, phisf1.2, and phisf3.33 belonged to the Myoviridae family with feature long, contractile tails and hexagonal head. Phages phisf3.21 and phisf3.10T appeared to have filamentous shape and produced turbid plaques, which is a characteristic of phages from the Inoviridae family. Phage phiort11 is a member of the Podoviridae and was selected for further characterization and genome sequencing. phiort11 contained linear, double-stranded DNA with a length of 75239 bp and 103 putative open reading frames. BLASTP analysis revealed strong similarities to Escherichia phage N4 and other N4-like phages. This is the first report of filamentous and N4-like phages that infect Sinorhizobium meliloti.